Impacts of National Government-Community Developments Funds (CDF), Older Persons Cash Transfer (OPCT) and National Health Insurance Fund (NHIF) in Reducing Urban Poverty in Eldoret Town, Kenya - Kipkemei, F. B.; Cheserek, G.; Ondari, G. (Africa Environmental Review Journal, 2020)
Poverty for many years has been associated with rural areas and little focus has been cast on urban poverty and its effects. A study to assess inequality and urban poverty in Kenya estimated the percentage of urban poverty in Eldoret town to be at 35.5% with a population of 79.9% living in core urban region and those that lived in the peri-urban regions were 20.1%. World bank estimates that the pace of poverty reduction in Kenya is only at 1% per a year. At such a rate, poverty eradication can only be a dream. On Sustainable Development Goals of eliminating poverty, Kenya has a similar goal through vision 2030 to have poverty reduced to lower levels. The purpose of this study was to assess impacts of National Government –Constituency Development Funds (CDF), Older Persons Cash Transfer (OPCT) and National Health Insurance Fund (NHIF) in reducing urban poverty in Eldoret town, Kenya. The study designed the research objectives and questions in a manner to help establish the impacts of the poverty reduction strategies. Literature was reviewed to establish facts as they are or have been in other countries. The descriptive research design was adopted for this study to describe the situation as it is and propose solutions to the poverty reduction strategies. Fischer’s formula was used and gave a sample size of 273 respondents who formed government officials and household heads of low-income estates of Langas, Kamukunji and Munyaka. The study used cluster sampling for 200 household heads in the three low income estates, snowball sampling techniques to identify 58 respondents from beneficiaries of OPCT and purposive sampling technique to obtain data from 15 key informants. Questionnaires and interviews were the primary tools for data collection. Pilot testing was carried out to check for reliability and validity of the tools. Ethical considerations were equally observed where confidentiality of respondents was secured. Data was managed using SPSS Version 23 and analyzed using Descriptive Statistics. The results were presented using frequency tables, chi-square and pie charts. The study found out that all the 58 respondents of OPCT were beneficiaries of the “Older persons’ cash transfer (OPCT)”. OPTC has played a major role in poverty reduction at a rate of (84.5%) by promoting sustainable income for its members for buying food stuff as well as investing in micro-businesses like practising domestic poultry farming. OPTC has also improved the education of the dependences’ siblings through payment of school fees for them, buying of books and examination fees in cost sharing arrangements with learning institutions. Health of the beneficiaries and their dependence has been promoted by up to (49%) through spending the OPTC cash in hospital bills where the member is not covered by NHIF or absence of drugs in their NHIF chosen facilities. OPTC has also enhanced security of securing a rental house by paying for monthly rent in urban areas. However, beneficiaries never relied fully on this kitty to meet their daily family needs. Constituent Development Funds (CDF) has promoted education of all learners both in primary, secondary and tertiary institutions by a rate of (98%) though it does not pay for school fees of learners. It has not done much in promoting income, promotion of good health and employment for sustainable income. Therefore, CDF was not the most common livelihood strategy among Eldoret residents. “National Hospital Insurance Fund” (NHIF), provided health insurance for most respondents and their dependants. It has improved health of its beneficiaries by (69.0%). It has improved the maternal health of the mother and the baby both pre- natal and post-natal by (89.3%) therefore improving the health and security of beneficiaries. NHIF has not done much in matters Education and sustainable income of its beneficiaries. Furthermore, monthly premiums are not affordable to all. Older Persons Cash Transfer, National Government Constituency Development fund and National Health Insurance Fund (NHIF) would play a great role in reduction of poverty in the society if only managed well by ensuring proper funding and transparency for reasons of accountability. This would lead to a significant change in the lifestyles of the urban poor measured by the changes in Social Economic Status indicators (SES) such as education, health facilities, security and empowerment.